Towarzystwo Pedagogiczne we Lwowie w latach 1868–1906 (wybrane zagadnienia) - Przeniosło, Małgorzata (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2014)
Founded in 1868 the Pedagogical Society in Lviv was a professional-scientific association of the Galician teachers. The Society dealt with the development of education (especially elementary), teachers’ subsistence, their self-education and professional development. Among the members of the organization were also representatives of other communities, especially those interested in the improvement of the educational system in Galicia. The main office in Lviv supervised the local branches whose number grew rapidly. In 1868 there were already 19 branches established. According to the data from the 1871/1872 school year, the Society had 2,500 members. The organization published its own weekly entitled „School”. In 1906 it was decided to change the name – the Pedagogical Society was transformed into the Polish Pedagogical Society. Thus, the national character of the organization was defined more clearly. However, at that time the Ukrainian teachers had already created their own association in Eastern Galicia. The Polish Pedagogical Society existed until 1921.